2008
DOI: 10.1136/vr.163.21.625
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the nuclear morphology of the sperm of 10 bulls and their fertility

Abstract: The relationships between the fertility and nuclear morphology, chromatin maturity and chromatin condensation of the sperm of three bulls with a calving rate over a year of more than 65 per cent, four bulls with a calving rate between 65 per cent and 35 per cent, and three bulls with a calving rate of less than 35 per cent were studied. The sperm nuclei were stained with the Feulgen reaction, and chromatin condensation and maturation were evaluated in situ by staining with toluidine blue and acid aniline blue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(54 reference statements)
2
10
0
Order By: Relevance
“…2a). We propose that these sperm nuclei were diploid (2n) in agreement descriptions made in other species (Gledhill, 1965;Giuliano et al, 1997;Ferrari et al, 1998;Vieytes et al, 2008). The size of sperm nuclei of the third subpopulation was greater than that of the haploid and diploid nuclei and the intensity of the Feulgen colouration was similar to that of the diploid nuclei (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…2a). We propose that these sperm nuclei were diploid (2n) in agreement descriptions made in other species (Gledhill, 1965;Giuliano et al, 1997;Ferrari et al, 1998;Vieytes et al, 2008). The size of sperm nuclei of the third subpopulation was greater than that of the haploid and diploid nuclei and the intensity of the Feulgen colouration was similar to that of the diploid nuclei (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The percentage of diploid spermatozoa observed in human semen from fertile men is approximately 0.3% and they originate 8.3% of diandric triploids (Codina-Pascual et al, 2006). Some authors have observed that the shape and size of bovine diploid spermatozoa are very similar to those of normal spermatozoa, and that when they are stained with the Feulgen reaction, diploid spermatozoa are notoriously darker than normal and have a post-acrosomal zone broader than normal (Gledhill, 1965;Ferrari et al, 1998Ferrari et al, , 2006Vieytes et al, 2008). A similar observation has been made in llama diploid spermatozoa (Giuliano et al, 1997).…”
Section: Introductionmentioning
confidence: 92%
“…Thin smears for light microscopy were made from the fixed semen samples and stained with Wright's stain (Rapidiff, Clinical Sciences Diagnostics, Johannesburg, South Africa) before viewing with a 100x oil immersion lens using both bright field and phase contrast microscopy. Smears were also stained with the Feulgen stain and acidic aniline blue according to the methods described by Vieytes et al [30] to evaluate the degree of chromatin condensation. The incidence of the two defects was determined by examining the smears using a 100x oil immersion objective and counting the number 5 of abnormal spermatozoa present in a total of 300 cells for each bird.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies using the ANBL test have been conducted in humans, suggesting its predictive value for male fertility (Auger et al 1990, Hammadeh et al 2001. Relatively few studies have examined the association of the ANBL test and bull fertility (Vieytes et al 2008). Among the species, the percentage of ANBL-positive sperm cells has been found to be variable, such as 1% in mice (Shokri et al 2013), 10% in cats (Hingst et al 1995), 10% in rabbits (Steger et al 2005), and 50% in roosters (Santiago-Moreno et al 2009).…”
Section: Discussionmentioning
confidence: 99%